The Effect of Computerized-Adaptive Test on Reducing Anxiety Towards Math Test for Polytechnic Students - S., Mohd-Ali; N., Norfarah; J.I., Ilya-Syazwani; I., Mohd-Erfy (Journal of Technical Education and Training, 2019)
Although much work has been done on computerized-adaptive test (CAT) in reducing anxiety towards exam, CAT in Malaysian educational setting is less explored among educational researchers. Some of the reason is due to technical difficulty in developing, maintaining the testing bank items, and insufficient hardware facilities for huge number of examinees in Malaysia. Hence, traditional assessment method is preferred to assess students’ performance. However, traditional assessment induced students’ anxiety towards examination. The effect of anxiety towards mathematics examination has deteriorated students’ performance particularly at polytechnics that offers technical-vocational-education-and-training (TVET). Therefore, this study aimed to examine the effect of CAT in reducing examinees’ anxiety towards mathematics examination in comparison with traditional testing approaches at three polytechnics in northern Malaysia that offered diploma certification in engineering. These three polytechnics were chosen because it is classified as conventional and accessibility of the researchers to these samples. In order to ensure the homogeneity of the samples, students in their first year of study who enrolled in engineering mathematics were chosen. This research used quasi-experimental research method with non-equivalent control group design involving 300 students. Item-response-theory was used to describe examinees’ interaction with the test items. The results show that CAT has reduced examinees’ anxiety towards mathematics test in comparison to those of traditional testing. This study implies that CAT has benefited students in term of reducing their anxiety towards mathematics examination in the case of Malaysian polytechnics students, and has the potential to be adopted in TVET because it improves testing efficiency.